(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
The influence of perceived job tension on stress reaction among hospital and university workers in Nigeria was the focus of this study. 160 participants randomly selected from hospital and university settings were used for the study. The age of the participants ranges between 25 years and 50 years with a mean age of 35. Four hypotheses were tested and results shows that job stress is directly proportional to personal distress. Also, no significant difference was found in the job related tension between hospital and university workers. Result of this study shows that females have the same perception of work environment and they react to stress in the same manner. However, a significant difference exists in the level of stress between female and male university workers. Key words : 1. Job tension: The rigours and stress workers undergo on the job. 2. Stress reaction: It the way workers react to stress on the job. This could be positive or negative. 3. Stress: It is the unfavorable conditions that workers pass through in the course of discharging their job duties. 4. Stressors: These are conditions that bring about stress on the job. Â DOI = 10.3329/bjsir.v43i3.1150 Bangladesh J. Sci. Ind. Res. 43(3), 353-358, 2008